Vitamin B12, folate, and homocysteine levels in children and adolescents with obesity: a systematic review and meta-analysis - Juan R. Ulloque-Badaracco; Esteban A. Alarcon-Braga; Enrique A. Hernandez-Bustamante; Enrique A. Hernandez-Bustamante; Beatrix M. Von-Koeller-Jones; Miguel Huayta-Cortez; Esduardo Saavedra-Custodio; Percy Herrera-Añazco; Vicente A. Benites-Zapata (Frontiers in Public Health)
Background and aimsChildhood and adolescent obesity is a global public health concern. Obesity induces several metabolic disturbances. Several studies have explored the association of vitamin B12, folate, and homocysteine (Hcy) with obesity. This study aimed to synthesize the available evidence regarding the differences in serum levels of vitamin B12, Hcy, and folate among children or adolescents with and without obesity.MethodsA random-effects meta-analysis using the Sidik-Jonkman method and corrected 95% confidence interval (CI) using the truncated Knapp-Hartung standard errors was used for all meta-analyses. Standardized mean difference (SMD) with the corresponding 95% CI was used as the only effect size. The Cochran’s Q test and the I2 statistic were used to evaluate between-study heterogeneity. Publication bias was assessed using funnel plots and the Egger test.ResultsTwenty studies were included with a combined study population of 7,791 patients. There were no significant differences between children/adolescents with and without obesity with respect to serum vitamin B12 levels (SMD: −0.24; 95% CI: −0.53 to 0.06; p > 0.05, I2 = 74.93%) and folate levels (SMD: −0.12; 95% CI: −0.29 to 0.06; p > 0.05, I2 = 19.6%). However, children/adolescents with obesity had significantly higher Hcy levels compared to counterparts without obesity (SMD: 0.77; 95% CI: 0.39 to 1.14; p < 0.001, I2 = 86.4%).ConclusionChildren and adolescents with obesity had higher Hcy levels than those without obesity. However, no significant differences were found for vitamin B12 and folate levels. Hcy may play a role in the development of obesity in this population.